Development and Optimization of an Immunoassay for the Detection of Antibodies Against SARS-CoV-2 with In-house Recombinant RBD Protein - Ratu, Safira Pinaka Pramestika; Mariya, Silmi; Noviana, Rachmitasari; Saepuloh, Uus; Darusman, Huda Salahudin (UI Scholars Hub, 2022)
COVID-19 caused by SARS-CoV-2 poses a major threat to the global community, particularly in Indonesia. Countermeasures to prevent the spread of this disease have also been implemented, including the implementation of a vaccination program. An immunoassay technique that can be used to analyze antibodies that might develop following vaccination is the indirect enzyme-linked immunosorbent assay (ELISA). We produced the recombinant spike protein used in this study. The optimization comprised adjusted concentrations of spike recombinant protein (5 and 10 ng/mL), blocking agent (2.5% and 5%), and conjugate (1:1000 and 1:5000). The optimal conditions in this study included a spiked concentration of 10 ng/mL, a blocking agent concentration of 5%, sample dilution of 1:33, and a conjugate concentration of 1:1000. The intra-assay value of this optimized indirect ELISA was 7.3, and the inter-assay value was 5.3. The commercial MyBioSource kit and immunodiagnostic were utilized as a reference in the T-test, with P-values of 0 and 0.313, indicating that the recombinant protein in-house ELISA kit in this study demonstrated the same ability as the commercial immunodiagnostic kit in detecting SARS-CoV-2 antibodies, allowing it to be used for post-vaccination efficacy evaluation.